Genetic characterization of human echinococcosis in Southern Punjab, Pakistan - Basharat, Nosheen; Khan, Jadoon; Ullah, Irfan; Shah, Aamer Ali; Ali, Ijaz (Frontiers in Cellular and Infection Microbiology, 2023)
Echinococcosis is a neglected tropical zoonotic infection of the human and livestock population. In Pakistan, the infection has a historical background, with limited data on molecular epidemiology and genotypic characterization in Southern Punjab, Pakistan. The current study is aimed at molecular characterization of human echinococcosis in southern Punjab, Pakistan. A total of 28 human echinococcal cysts with demographic characteristics were collected from surgically treated patients and further processed for DNA isolation to probe Nad1 and Cyt-b genes followed by sequencing and phylogenetic analysis for genotypic identification, respectively. The majority of the echinococcal cysts were from the males (60.7%) as compared to female. The liver (60.71%) was the most infected organ followed by lungs (25%), spleen (7.14%), and mesentery (7.14%). Molecular and genotypic identification through sequencing and phylogenetic tree analysis showed that most 85.7% (24/28) of the cysts were caused by species Echinococcus granulosus sensu stricto (E. granulosus s.s) (G1 and G3) and 10.8% (3/28) by Echinococcus multilocularis (E. multilocularis) followed by Echinococcus canadensis (E. canadensis) (G6/7) 01/28 (3.5%), respectively. The current study concluded that majority of the human infection was caused by E. granulosus s.s. followed by E. multilocularis and E. canadensis (G6/G7). Genotypic characterization among both human and livestock populations is needed to explore the genetic diversity of echinococcosis.